2016
DOI: 10.1111/jgs.14246
|View full text |Cite
|
Sign up to set email alerts
|

Is This Broken Bone Because of Abuse? Characteristics and Comorbid Diagnoses in Older Adults with Fractures

Abstract: OBJECTIVES To examine the relationship between individual characteristics and potential correlates of elder abuse in older adults who present with fractures. DESIGN Cross-sectional analysis of deidentified data extracted from medical records. SETTING Academic medical center. PARTICIPANTS Individuals aged 65 and with a primary diagnosis of any fracture admitted to an outpatient department or emergency department (ED) in a single southern California medical center over a 36-month period (N = 652). MEASUR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 28 publications
0
18
1
Order By: Relevance
“…Comparing the cases of fatal trauma in this study with those of nonfatal trauma to understand which of these fracture patterns and morphologies, if any, may directly contribute to the fatality would further inform forensic practitioners with their interpretations of the circumstances of a fatal low free fall. Furthermore, comparing and contrasting these fractures with the skeletal BFT resulting from other types of falls and other BFT mechanisms such as physical assaults (e.g., ) would allow forensic anthropologists and pathologists to begin to address those complex BFT questions pertaining to the mechanism of injury.…”
Section: Resultsmentioning
confidence: 99%
“…Comparing the cases of fatal trauma in this study with those of nonfatal trauma to understand which of these fracture patterns and morphologies, if any, may directly contribute to the fatality would further inform forensic practitioners with their interpretations of the circumstances of a fatal low free fall. Furthermore, comparing and contrasting these fractures with the skeletal BFT resulting from other types of falls and other BFT mechanisms such as physical assaults (e.g., ) would allow forensic anthropologists and pathologists to begin to address those complex BFT questions pertaining to the mechanism of injury.…”
Section: Resultsmentioning
confidence: 99%
“…In the latter case, it is really difficult to discern between an elder's proneness to falling and a caregiver's intentional lack of vigilance. These differences explain why the substantiation rate of referrals and calls for EN is very low (Gironda, Nguyen, & Mosqueda, ).…”
Section: Elder Neglect a Relatively Recent Conditionmentioning
confidence: 99%
“…[3] Despite this, studies in the field are estimated to be 20 years behind those for domestic violence and child abuse. [4] To date, Indonesia is yet to conduct a national review for the prevalence of nonfatal elder abuse. [5] Prior studies have identified 13 individual forensic markers linked to elder abuse and neglect.…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that finding a risk factor of abuse with forensic markers prompts for further investigation. [4] Another research on community-dwelling elders discovered individual level risks to be psychiatric illness, cognitive impairment, psychological problems, behavioural problems, functional dependency, poor physical health and frailty. [6] This study is aimed at building on existing research in the field of forensic markers of elder abuse and attempt to prescreen elder abuse and neglect within Sanglah General Hospital, Bali.…”
Section: Introductionmentioning
confidence: 99%